Faktor predisposisi yang berhubungan dengan perilaku merokok pada mahasiswa - Widyawati Widyawati; Juwi Athia Rahmini; Sri Dhamayani (Holistik Jurnal Kesehatan, 2022)
Background: Smoking habits provide enjoyment for smokers but can have a bad impact on smokers themselves and those around them so the smoking problem has become a national problem where Indonesia is still the third country with the most active smokers in the world.Purpose: To find out what predisposing factors are related to smoking behavior in students of the D3 Electrical Technology Study Program at STIKes Binalita Sudama Medan.Method: This type of research is quantitative research, with a cross-sectional approach. The population is students, the sample is 60 respondents. The analysis used univariate, bivariate, and multivariate. The statistical test used is the Chi-Square test and the multiple linear regression test.Results: Respondents who smoked were 29 respondents (48.3%). The results of the bivariate analysis showed that the variables related to smoking behavior in respondents were, level of knowledge (p = 0.000), attitude (p = 0.002), action (p = 0.001), psychological reasons: felt difficulty in learning (p = 0.040), seen cool (p = 0.009), wants to be accepted in the association (p = 0.020).Conclusion: There is a significant relationship between predisposing factors (knowledge, attitudes, actions and psychological reasons) with smoking behavior in students. The most dominant factor related to smoking behavior in respondents is knowledge (B value = 0.375 and p = 0.000).Keywords: Smoking Behavior; Knowledge; Attitudes; StudentPendahuluan : Kebiasaan merokok dianggap dapat memberikan kenikmatan bagi perokok, tetapi dapat menimbulkan dampak yang buruk bagi perokok itu sendiri maupun orang di sekitarnya, sehingga masalah rokok sudah menjadi masalah nasional dimana Indonesia masih menjadi negara ketiga dengan perokok aktif terbanyak di dunia. Tujuan : Mengetahui faktor predisposisi apa saja yang berhubungan dengan perilaku merokok pada mahasiswa Program Studi D3 Teknologi Elektro Medis STIKes Binalita Sudama Medan,Metode : Penelitian kuantitatif, dengan pendekatan cross sectional. Populasinya mahasiswa, dengan sampelnya 60 responden. Analisis yang digunakan univariat, bivariat dan multivariat. Uji statistic yang digunakan adalah uji Chi Square dan uji regresi linear bergandaHasil : Responden yang merokok sebanyak 29 responden (48,3%). Hasil analisa bivariat didapatkan variabel yang berhubungan dengan perilaku merokok pada responden adalah, tingkat pengetahuan (p=0,000), sikap (p=0,002), tindakan (p=0,001), alasan psikologis: merasa kesulitan dalam pelajaran (p=0,040), terlihat keren (p=0,009), ingin diterima dalam pergaulan  (p=0,020).Simpulan : Terdapat hubungan bermakna antara faktor predisposisi (pengetahuan, sikap, tindakan dan alasan psikologis) dengan perilaku merokok pada mahasiswa. Faktor yang paling dominan berhubungan dengan perilaku merokok pada responden adalah pengetahuan (Nilai B = 0,375 dan p = 0,000)